2016
DOI: 10.1097/md.0000000000004399
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multidisciplinary heart failure disease management programme on 1-year mortality

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Recruiting centres included all main public and private hospitals and cardiology practices in Lorraine (2.3 million inhabitants). Consistent with pre‐existing evidence, the ICALOR programme was proven to decrease both HF hospitalizations and all‐cause mortality, stabilizing HF hospitalization rate progression in Lorraine, whereas those observed overall in France progressed by approximately 3.5% annually. These results were in line with the results of previous randomized trials, and confirmed the substantial benefit of HF‐DMP on both outcomes of interest in an unselected population of chronic HF patients using observational designs.…”
supporting
confidence: 67%
“…Recruiting centres included all main public and private hospitals and cardiology practices in Lorraine (2.3 million inhabitants). Consistent with pre‐existing evidence, the ICALOR programme was proven to decrease both HF hospitalizations and all‐cause mortality, stabilizing HF hospitalization rate progression in Lorraine, whereas those observed overall in France progressed by approximately 3.5% annually. These results were in line with the results of previous randomized trials, and confirmed the substantial benefit of HF‐DMP on both outcomes of interest in an unselected population of chronic HF patients using observational designs.…”
supporting
confidence: 67%
“…The EPICAL2 study was an observational, prospective, multicenter, and population‐based cohort study, previously described in detail elsewhere . Briefly, the cohort involved 21 volunteer hospitals all over the Lorraine region of northeast France (population 2 350 000 according to the 2012 census), which included patients hospitalized for acute HF or acute HF developing during hospitalization from October 2011 to October 2012.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of recruitment and patient characteristics have been already published elsewhere [7,8]. In brief, this cohort (EPICAL2, NCT02880358) included 2254 patients who were hospitalized in the Lorraine region of northeast France (2,350,000 inhabitants, according to the 2012 census) for acute HF between October 2011 and October 2012 and followed for 1 year after hospital discharge.…”
Section: Participantsmentioning
confidence: 99%
“…The type of statin could be any of the following: rosuvastatin, pravastatin, atorvastatin, simvastatin, lovastatin, fluvastatin, cerivastatin and pitavastatin. Besides sociodemographic and clinical data, treatment data were collected by standardized forms at inclusion, during the index hospitalization and at discharge [7,8]. The baseline characteristics of included patients are reported in Table 1.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation